2023
DOI: 10.3389/fgene.2022.1089389
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a QTL associated with sucrose content in peanut kernels using BSA-seq

Abstract: As an important factor affecting the edible quality of peanut kernels, sucrose content is a complex quantitative trait regulated by multiple factors. In this study, an F2 segregating population and a recombinant inbred line (RIL) population, derived from a cross between the high sucrose content variety Jihuatian 1 and the low sucrose content line PI478819, were used as materials to map a quantitative trait locus (QTL) associated with sucrose content in peanut kernels. Four QTLs were initially located on chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Epigenetic modifications, specifically DNA methylation, have been elucidated as pivotal regulatory mechanisms influencing peanut seed development. Comparative analyses have demonstrated global methylation changes accompanying seed development, with significant correlations between methylation levels and gene expression, particularly in pathways related to seed size and oil content (Liu et al, 2022;Li et al, 2023). These findings suggest that epigenetic regulation plays a substantial role in modulating seed trait expression.…”
Section: Deciphering Peanut Seed Development Based On Proteomic Metab...mentioning
confidence: 94%
See 1 more Smart Citation
“…Epigenetic modifications, specifically DNA methylation, have been elucidated as pivotal regulatory mechanisms influencing peanut seed development. Comparative analyses have demonstrated global methylation changes accompanying seed development, with significant correlations between methylation levels and gene expression, particularly in pathways related to seed size and oil content (Liu et al, 2022;Li et al, 2023). These findings suggest that epigenetic regulation plays a substantial role in modulating seed trait expression.…”
Section: Deciphering Peanut Seed Development Based On Proteomic Metab...mentioning
confidence: 94%
“…Fine-mapping of this QTL revealed a ~0.8-Mb genomic region harboring two annotated genes influencing oil synthesis, providing vital insights into the genetic determinants of oil-related traits in peanut. Employing BSA-seq technology, Guo et al (2023) uncovered four QTLs for sucrose content on chromosomes A03 and A06, while Wang et al (2024) further identified two homologous QTLs on chromosomes A06 and B06, providing valuable information on the genetic factors impacting this essential trait. Furthermore, studies on color traits identified key genes controlling red testa color.…”
Section: Qtl Mapping and Gwas Analysis Of Peanut Seed-related Traits ...mentioning
confidence: 99%
“…Genetic analysis suggested that sucrose content in peanut kernels is controlled by two additive–dominance–epistasis major genes plus an additive–dominance–epistasis polygene ( Qin et al., 2021 ). However, a lack of favorable alleles or genes has hindered breeding progress, given that the sugar content of seeds is influenced by various factors, including abiotic and biotic stresses, environmental conditions such as temperature, soil moisture, freezing, seed maturity, growth conditions, and genotype ( Maughan et al., 2000 ; Pattee et al., 2000 ; Knizia et al., 2023 ; Guo et al., 2023b ). Quantitative trait locus (QTL) mapping is a powerful method to identify alleles or genes controlling complex traits.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gangurde et al [ 35 ] also used a RIL population (Chico × ICGV02251) and detected seven QTLs associated with HSW in three years, responsible for 6.69–21.29% of PVE. Guo et al [ 36 ], using a RIL derived from Zhonghua 5 and ICGV 86699, identified 15 QTLs for HSW across six settings, explaining a phenotypic variation comprising 4.08–17.89%. Within these QTLs, only three displayed main effects.…”
Section: Introductionmentioning
confidence: 99%